Pentingnya Digital Forensik sebagai Upaya untuk Menganalisa Barang Bukti Elektronik Terhadap Proses Pembuktian Tindak Pidana Informasi dan Transaksi Elektronik - Rosmaida, Erviyanti; Bakhtiar, Handar Subhandi (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The purpose of this study is to review and analyze digital forensic regulations in the process of proving criminal acts in court, and to review and analyze how the implementation of digital forensic examinations as an effort to analyze electronic evidence against the process of proving criminal acts of information and electronic transactions. Then the research method used is the normative legal method. Normative legal research is carried out by examining the regulations in positive law which are researched normatively to be used as a source of legal material. In its preparation, the author obtained data in the form of primary legal materials, secondary legal materials, and tertiary legal materials. Primary legal materials are obtained from laws and regulations and other regulations in force in Indonesia, secondary legal materials are obtained from books, journals, and the internet as supporting materials, and tertiary legal materials are obtained from the Big Indonesian Dictionary (KBBI), encyclopedias, and others. The results of the study show that digital forensic science plays an important role in the proof process. Regarding valid evidence, it is regulated in Article 184 paragraph (1) of the Criminal Procedure Code, which stipulates 5 (five) types of valid evidence in criminal procedure law, namely: witness statements, expert statements, letters, clues, and statements from the accused. Then, digital forensics has an important role in the process of proving a crime. With this, its position not only strengthens the charges that have been filed against the accused, but is also intended to catch the perpetrators of the crime. Digital forensics plays an important role in the process of proof. In the process of proof, in general, digital forensics has five stages, namely: Identification, preservation, analysis, data reduction and filtering, and reporting. Identification is the first stage carried out in order to find out the location of the evidence and how the evidence is stored. After going through these stages, the next stage is preservation. Data preservation is a step taken to ensure that the data that has been obtained has been stored and secured to maintain the authenticity of the evidence. After the data has been successfully obtained, the next step is to analyze the data. The analysis stage in this case refers to interpretation and reconstruction in order to draw conclusions about the evidence that has been collected. After conducting the analysis, the next stage is data reduction and filtering.